PENGARUH SISTEM TANAM DAN PEMANGKASAN TANAMAN TERHADAP PERTUMBUHAN SERTA HASIL JAGUNG DAN KEDELAI - Arifin, Z.; , Suwono; Arsyad, Darman M (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
The Influence of Cropping Systems and Plant Trimming on Growth and Yield of Maize and Soybean. This study aimed to determine the effect of monoculture and intercropping systems and plant trimming on growth and yield of maize and soybean as well as farm income. The experiment was conducted in rainfed lowland at Mojosari Experimental Farm, Mojokerto Regency, East Java during the late dry season in 2012. Randomized block design with nine treatments of planting systems and three replications was used in this experiment. The planting system tested were: (1) Monoculture of soybean with planting space of 40 cm x 15 cm, (2) Monoculture of maize with planting space of 75 cm x 20 cm, without trim, (3) Monoculture of maize with planting space of 75 cm x 20 cm, and trimming the leaves and stems above the cob, (4) Intercropping of soybean-maize (90/60 cm x 20 cm, without trimming), (5) Intercropping of soybean-maize (90/60 cm x 20 cm, trimming the leaves and stems above the cob), (6) Intercropping of soybean-maize (150 cm x 20 cm, without trimming), (7) Intercropping of soybean-maize (150 cm x 20 cm, trimming the leaves and stems above the cob), (8) Intercropping of soybean-maize (180/120 cm x 20 cm, without trimming), (9) intercropping of soybeans-maize (180/120 cm x 20 cm, trimming the leaves and stems above the cob). The results showed that the intercropping system affected the growth and yield of soybean and maize compared to monoculture system. The intercropping system increased the plant height, but reduced the number of pod, seed, node, branch and seed yield of soybean compared the monoculture. Plant height, cob length, cob diameter, 100 seed weight, and yield of maize in intercropping decreased compared to those of monoculture system. Based on land equivalent ratio, total yield and net income, the intercropping soybean-maize with plating space of 150 cm x 20 cm with trimming the leaves and stems above the cob would be suggested and prospective to be developed in the farmerâs fields. Key words: Soybean, maize, intercroppingPenelitian bertujuan untuk mengetahui pengaruh sistem tanam monokultur dan tumpangsari kedelai-jagung dan pemangkasan tanaman jagung terhadap pertumbuhan dan hasil tanaman serta pendapatan usahatani. Penelitian dilaksanakan di lahan sawah tadah hujan, KP. Mojosari, Kabupaten Mojokerto, Jawa Timur pada MK I 2012. Rancangan percobaan yang digunakan adalah acak kelompok dengan tiga ulangan dan sembilan perlakuan. Perlakuannya adalah sistem tanam, yaitu: (1) monokultur kedelai dengan jarak tanam 40 cm x 15 cm, (2) monokultur jagung dengan jarak tanam 75 cm x 20 cm, tanpa pangkas, (3) monokultur jagung dengan pangkas daun bawah dan batang diatas tongkol, (4) tumpangsari kedelai-jagung dengan jarak tanam 90/60 cm x 20 cm, tanpa pangkas daun, (5) tumpangsari kedelai-jagung dengan jarak tanam 90/60 cm x 20 cm dengan pangkas daun bawah dan batang diatas tongkol, (6) tumpangsari kedelai-jagung dengan jarak tanam 150 cm x 20 cm, tanpa pangkas daun, (7) tumpangsari kedelai-jagung dengan jarak tanam 150 cm x 20 cm, pangkas daun bawah dan batang diatas tongkol, (8) tumpangsari kedelai-jagung dengan jarak tanam 180/120 cm x 20 cm, tanpa pangkas daun, (9) tumpangsari kedelai-jagung dengan jarak tanam 180/120 cm x 20 cm, pangkas daun bawah dan batang diatas tongkol. Hasil penelitian menunjukkan bahwa sistem tumpangsari kedelai-jagung menyebabkan tanaman kedelai bertambah tinggi, tetapi terjadi penurunan dalam jumlah polong, jumlah biji, jumlah buku, jumlah cabang, dan hasil biji. Sistem tumpangsari juga menyebabkan terjadinya penurunan tinggi tanaman jagung, panjang tongkol, diameter tongkol, bobot 100 biji, dan hasil biji. Berdasarkan nilai LER (Land Equivalent Ratio), total hasil setara kedelai, dan pendapatan (keuntungan) usahatani, maka sistem tanam tumpangsari kedelai-jagung pada jarak tanam 150 cm x 20 cm dengan pemangkasan daun bawah dan batang di atas tongkol pada umur 80 hari prospektif untuk dikembangkan di lahan petani. Â Kata kunci: Kedelai, jagung, tumpangsari